ASK120067 (limertinib) exerts pre-clinical anti-tumor activity by inhibiting EGFR exon20 insertion - Zhang, Tao; Feng, Fang; Tong, Linjiang; Chan, Shingpan; Chen, Yi; Li, Yan; Song, Peiran; Liu, Yingqiang; Bai, Gang; Lai, Mengzhen; Ning, Yi; Wang, Yanan; et al. (Frontiers in Drug Discovery, 2022)
Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) are classic strategies for the individualized treatment for patients with non-small cell lung cancer (NSCLC). However, EGFR exon20 insertion (EGFR 20ins) mutations, accounting for 6-12% of all EGFR mutant cases in NSCLC, are generally resistant to the reversible EGFR TKIs (such as gefitinib and erlotinib), which makes them challenging drug-targets in lung cancer. In our previous study, we identified ASK120067 (limertinib) as a novel 3rd-generation EGFR TKI targeting EGFR T790M mutation with promising clinical activities. Here, we accessed the potency of ASK120067 on EGFR 20ins activation and evaluated its in vitro and in vivo anti-tumor activity against EGFR 20ins driven tumor models. We found that ASK120067 showed potent inhibitory activity on TKI-resistant EGFR 20ins kinase. In TKI-resistant EGFR 20ins-dependent BaF3 cells, it dose-dependently suppressed EGFR phosphorylation, impeded cell proliferation, and induced cell apoptosis with much superior efficacy to gefitinib and erlotinib. Moreover, oral administration of ASK120067 decreased the level of phospho-EGFR 20ins and caused significant tumor regression in EGFR 20ins BaF3 xenograft model. These results presented the pre-clinical anti-tumor efficacy of ASK120067 in EGFR 20ins models and highlighted the potential value of ASK1200067 for the treatment of NSCLC patients harboring EGFR 20ins mutations.